2007
DOI: 10.1021/la063717u
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-Terminated Dendrimer-Coated Bioactive Interface for Protein Microarray:  High-Sensitivity Detection of Antigen in Complex Biological Samples

Abstract: Protein microarrays are promising tools that can potentially enable high throughput proteomic screening in areas such as disease diagnosis and drug discovery. A critical aspect in the development of protein microarrays is the optimization of the array's surface chemistry to achieve the high sensitivity required for detection of proteins in cell lysate and other complex biological mixtures. In the present study, a high-density antibody array with minimal nonspecific cellular protein adsorption was prepared usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 76 publications
0
80
1
1
Order By: Relevance
“…We realized that the availability and the lifetime of the NHS esters on the dendritic linker would determine the reaction efficiency and yields in the conjugation with the biomolecule that needs to be labeled. The activation reaction with EDC and NHS is most efficient at slightly acidic pH and usually performed in MES buffer at pH 4.7-6.0 [41,42,27]. With that in mind, we decided to explore on the effect of some other variables present in the EDC/NHS activation step such as the molar excess of NHS per COOH group, the ratio of the EDC/NHS co-reactants and the reaction time needed for the COOH activation.…”
Section: Optimisation Of Bioconjugationmentioning
confidence: 99%
See 1 more Smart Citation
“…We realized that the availability and the lifetime of the NHS esters on the dendritic linker would determine the reaction efficiency and yields in the conjugation with the biomolecule that needs to be labeled. The activation reaction with EDC and NHS is most efficient at slightly acidic pH and usually performed in MES buffer at pH 4.7-6.0 [41,42,27]. With that in mind, we decided to explore on the effect of some other variables present in the EDC/NHS activation step such as the molar excess of NHS per COOH group, the ratio of the EDC/NHS co-reactants and the reaction time needed for the COOH activation.…”
Section: Optimisation Of Bioconjugationmentioning
confidence: 99%
“…Multivalent dendrimers are attracting a great deal of interest for applications in biomedical diagnostics [27][28][29][30], pharmacology / drug delivery [31,32] [33], cancer research [34], and nanomedicine [35]. Their use in research is still unabated now, 30 years after their first reported synthesis by Vogtle [36].…”
mentioning
confidence: 99%
“…Polyethylene(glycol) derivatives are also known in surface chemistry as effective suppressors of non-specific binding of biomolecules [15][16][17][18]. Their function is associated less with electrostatic forces but rather with vast hydration and effects of change of configurational entropy when large molecules adsorb upon them.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, TEOS was grafted onto a Zeonor substrate and allowed to cross-link with molecules of acrylic acid. The polymerization reaction was initiated by plasma and resulted in the formation of exceptionally stable, hydrophilic film with high density of Ð COOH groups.Polyethylene(glycol) derivatives are also known in surface chemistry as effective suppressors of non-specific binding of biomolecules [15][16][17][18]. Their function is associated less with electrostatic forces but rather with vast hydration and effects of change of configurational entropy when large molecules adsorb upon them.…”
mentioning
confidence: 99%
“…DP-coated surfaces can load more proteins and more protein activity than planar surfaces. [64][65][66][67] Furthermore, we determined the relative amounts of dendrimer immobilized on the surface and monitored the enzymecatalyzed reactions using fluorescence microscopy by means of the fluorescent properties of the DP. 66 To prepare a DP-coated surface, the surface of a silicon wafer was covered with positively charged amine groups using 3-aminopropyltriethoxysilane deposited DP via electrostatic interaction in a silanization reaction (Figure 12).…”
Section: Dp-immobilized Surfaces For Diagnostic Toolsmentioning
confidence: 99%